BEARING CAPACITY AND SETTLEMENT ANALYSIS OF DRILLED PILE FOUNDATION AT THE ASN-4 IKN APARTMENT CONSTRUCTION PROJECT - Made Dodiek Wirya Ardana; I Made Aryatirta Predana; Ni Ketut Aprilia Kartiana Dewi (Universitas Udayana, 2025)
The relocation of the capital city requires the development of various essential infrastructures to support the functions of the National Capital. ASN-4 IKN Apartment is one of the vertical housing projects that implements land efficiency by constructing high-rise buildings. A thorough analysis of foundation bearing capacity and settlement is necessary, given the unique soil conditions and the lack of previous research in the area. If the foundation does not have sufficient bearing capacity, it may lead to settlement due to the loads applied above it. Therefore, both analyses are crucial during the planning process and should be monitored during implementation through load testing on drilled piles to obtain values for bearing capacity and settlement. This analysis aims to calculate and compare the bearing capacity and settlement of the foundation using analytical methods, the finite element method with the assistance of PLAXIS 2D software, and field load testing through the PDA Test. The ultimate bearing capacity results obtained from the Reese and Wright method are 1076,820 tons, with PLAXIS 2D software 805,576 tons, and from the PDA Test 727 tons. The percentage comparison of bearing capacity values between the Reese and Wright method and the finite element method against the PDA Test are 48,118% and 10,808%. Meanwhile, the settlement values using the empirical method are 10,082 mm, with PLAXIS 2D software 2,742 mm, and from the PDA Test 2,3 mm. The percentage comparison of settlement values between the empirical method and the finite element method against the PDA Test are 1,070% and 0,061%.